DAMPAK PENGALAMAN BERORGANISASI TERHADAP PERKEMBANGAN KARIR DAN JIWA KEPEMIMPINAN DI KALANGAN MAHASISWA (Studi Kualitatif di Kampus Institut Bisnis Muhammadiyah Bekasi) - DJIHADUL MUBAROK; EVA FAUZIANA (Develop: Jurnal Ekonomi Pembangunan, 2020)
This study discusses the impact of organizational experience while in college on career development and leadership spirit among students. Qualitative study by taking 84 students as respondents at the Bekasi Muhammadiyah Business Institute campus in the period February 2021. This study uses a questionnaire as the main tool in collecting opinions. The results of this study are, students who actively participate in student organization activities or when they are in the same school as OSIS, have a greater chance of being accepted for work, and have a wider perception of positive leadership styles